Mitigation of drought or a combination of heat and drought stress effects on canola by Thuricin 17, a PGPR-produced compound - Nazari, Mahtab; Smith, Donald L. (Frontiers in Sustainable Food Systems, 2023)
Plant growth promoting microorganisms (PGPMs) and specific compounds they produce have the capacity to mitigate the adverse affects of stressors on plants. An example in this regard is Thuricin 17 (Th17), a signal molecule produced by Bacillus thuringiensis NEB17 (Bt NEB17), a plant growth-promoting rhizobacterium. In this study, we aimed to determine the efficacy of Th17 in mitigating drought and the combination of drought and heat stress to improve canola (Brassica. napus [L.]) growth and development in controlled environment chambers. Two of the best Th17 concentrations, 10-9 (Th1) and 10-11 (Th2) M, were used either as seed treatment plus root drenching or foliar spray. Leaf area and biomass accumulation was increased by both application methods of Th1 under moderate and severe drought stress, whereas more promising results were seen from Th2-treated plants under combination of stressors. Additionally, root length, root surface and root volume were increased by 21, 22 and 23%, respectively, for plants grown from Th1 seed treatment plus root drenching, compared to controls under severe drought conditions. Moreover, SOD, POD and CAT contents were increased by spraying Th1 and Th2 under individual stresses and the combination of heat and drought, respectively. Accordingly, increases in physiological variables were observed for sprayed plants, which also had higher antioxidant contents. These results indicated that plant responses to the compound varied with concentration of Th17 and plant growth conditions. Specifically, when plants were grown under individual stress, either drought or heat, the higher level of Th17 was more effective whereas the lower dose demonstrated higher positive impacts under the combination of heat and drought. Regarding application method, both seed treatment plus root drenching and foliar spray, had the ability to assist plants in alleviating stresses through growth stimulatory mechanisms. Therefore, Th17 has potential to become an environmentally friendly biostimulant, particularly under stressful environmental conditions.